Peran Pemerintah dalam Mengatasi Kemiskinan di Kota Medan - Nova Amelia; Selfi Oktarahmadini; Anisa Harahap (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Poverty is a complex and multidimensional social issue, encompassing the inability of individuals to meet basic needs as well as access to education, healthcare, and decent employment. In the city of Medan, the challenge of poverty remains significant despite its role as an economic hub in North Sumatra. Various efforts have been made by the Medan City Government through social assistance programs, economic empowerment, and infrastructure improvements; however, challenges such as social inequality, limited job opportunities, and bureaucratic inefficiencies remain major obstacles. Additionally, ineffective coordination between the government, NGOs, and the private sector slows the achievement of poverty alleviation goals. Therefore, a holistic approach that includes improvements in education, healthcare, and private sector involvement in local economic development is needed to address poverty sustainably in Medan.